2022
DOI: 10.3389/fimmu.2022.820524
|View full text |Cite
|
Sign up to set email alerts
|

P2Y1R Ligation Suppresses Th17 Cell Differentiation and Alleviates Colonic Inflammation in an AMPK-Dependent Manner

Abstract: P2Y1 receptor is a G-protein-coupled receptor that plays a critical role in the immune response of inflammatory bowel diseases. However, its regulatory effects on CD4+ T cell response have not been fully elucidated. The study aimed to characterize the role of P2Y1R in Th17 cell differentiation and colonic inflammation. Our results demonstrated that P2Y1R was significantly increased in the splenocytes of colitic mice, which was positively associated with the expression of RORγt and IL-17A. P2Y1R deficiency sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…However, the data are different from what we observed upon P2Y 1 deficiency. In previous studies, P2Y 1 blockade and P2Y 1 deficiency did show comparable results (38,77,78), suggesting that the discrepancy we have observed now could be due to sepsis in general or the CLP model. As previous studies investigating either P2Y 1 deficiency or antagonism were performed almost exclusively in male mice (37, 38, 44, 77), our experiments were the first to investigate changes in inflammation levels in sepsis in female mice upon P2Y 1 blockade and compare them with the male counterpart.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…However, the data are different from what we observed upon P2Y 1 deficiency. In previous studies, P2Y 1 blockade and P2Y 1 deficiency did show comparable results (38,77,78), suggesting that the discrepancy we have observed now could be due to sepsis in general or the CLP model. As previous studies investigating either P2Y 1 deficiency or antagonism were performed almost exclusively in male mice (37, 38, 44, 77), our experiments were the first to investigate changes in inflammation levels in sepsis in female mice upon P2Y 1 blockade and compare them with the male counterpart.…”
Section: Discussionsupporting
confidence: 80%
“…There are studies investigating how P2Y 1 can regulate CD4+ differentiation in vivo and in vitro . P2Y 1 deficiency decreased CD4+ population growth and in particular Th17 differentiation during colonic inflammation ( 77 ). In vitro experiments in human PBMCs have shown that blocking P2Y 1 could modulate CD4+ cell activation ( 84 ).…”
Section: Discussionmentioning
confidence: 99%
“…Proteins from RAW 264.7 cells and colon tissues were extracted using RIPA buffer supplemented with protease and phosphatase inhibitors and subsequently subjected to immunoblotting analysis, as described in a previous study. 17 The primary antibodies utilized were Akt, p-Akt, p38, p-p38, ERK, p-ERK, JNK, and p-JNK, along with β-actin (Cell Signaling Technology, MA, USA). The intensity of the bands was quantified using ImageJ software.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…Colitis was copied in mice with 2% DSS drinking water, as in our previous study, 2 and then colitis mice were randomly divided into DSS model, cyclosporin A (CSA), and two GPS extract treated groups. At the same time, the vehicle control group without DSS was set up.…”
Section: Methodsmentioning
confidence: 99%
“…As one of the modern refractory diseases listed by the World Health Organization, the occurrence of inflammatory bowel disease (IBD) seriously affects the quality of life of patients. 1 , 2 To date, IBD is incurable, but its remission can be achieved and maintained with aminosalicylate, corticosteroids, immunosuppressants, and biologics. 3 , 4 However, the abovementioned IBD treatments have obvious defects, such as high side effects, high cost, repeated recurrence, and even aggravation.…”
Section: Introductionmentioning
confidence: 99%